Pepali Ki Ageng Selo sebagai Konsep Etika Kewarganegaraan - Wawan Shokib Rondli (Jurnal Rontal Keilmuan Pancasila dan Kewarganegaraan, 2021)
The purpose of this research was to explore and uncover the values of Pepali Ki Ageng Selo as the ethics of citizenship. The research’s method used qualitative philosophical approach with factual historical research method conducted by philosophical investigation which followed the way and direction of mind presented in the book entitled Pepali Ki Ageng Selo through interpretation, induction and deduction, interent coherence, holistic, historical continuity, idealization, comparison, heuristika, inclusion or analogical language, description, special methods and reflections of personal researchers. The results of the study revealed the values of Pepali Ki Ageng Selo as the ethics of citizenship. These values were the ethics of citizenship in the life of a nation consisted of (1) socio-cultural ethics; (2) political and governmental ethics; (3) economic and business ethics; (4) scientific ethics; and (5) environmental ethics. These values were the form of orders and prohibitions that should be implemented by citizens in order to achieve happiness. Thus, the results of this study can be a reference in the implementation of Citizenship Education, especially in the context of Pancasila as a political and state ethics. Excavation of philosophical values taught through Pepali Ki Ageng Selo certainly in an effort to strengthen the values contained in the ideology of Pancasila.